Exploring Students’ Strategies in Developing Speaking Skill at the Eleventh Grade of SMA Al-Azhar Mandiri Palu - Arumdani, Retno; Kuliahana, Ana; Putri, Prisna (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The aim of this research was to describe the strategies used by the eleventh-grade student of SMA Al-Azhar Mandiri Palu and the challenges faced by the students in developing speaking skill. This research used a descriptive qualitative approach with five participants selected using purposive sampling technique. Data were collected through interview and document review. Data analysis used were data reduction, data display, and conclusion.The findings revealed that the students employed nearly all types of learning strategies as classified by O'Malley and Chamot. In metacognitive strategy, they utilized self-management, self-monitoring, and self-evaluation. For cognitive strategy, the students applied resourcing, repetition, transfer, keyword method, inferencing, note-taking, and summarizing. Meanwhile, for social-affective strategy, students used asking for clarification, cooperation, and self-talk. This research also revealed various challenges faced by students in developing speaking skill, which are environment challenge, nervousness, fear of judgment, pronunciation and vocabulary difficulty, and lack of confidence. The findings illustrated that learning strategies play an important role in the development of EFL students' speaking skill.